Using some methods to estimate the parameters and dependencies of the composite probit model (Exponential-Weibull) with a practical application - Hydr Rayd Talib (Iraqi Journal for Administrative Sciences, 2024)
This paper is Concerned on comparison between the Maximum Likelihood method (MLE) and the least squares method (OLS) to estimate the parameters and the Reliability of proposed distribution of the compound (exponential - Weibull) with three parameters. Using a standard for comparison is the absolute average errors. This paper applied to the real data collected from the public company Textile Industries in Wasit Governorate (Kut textile factory) and through the results obtained show that the greatest Method Maximum Likelihood is the best in the case of estimation the distribution parameters. While the reliability function estimate showed that the least squares method is the best.